2005
DOI: 10.1520/jai12984
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Volatiles Generated During the Selby-Noack Test by 31P NMR Spectroscopy

Abstract: A series of engine oil samples collected during a study of their Phosphorus Emission Index values were analyzed by 31P Nuclear Magnetic Resonance Spectroscopy. (The PEI analyses themselves were presented in an associated paper [1]). NMR spectra were generated to obtain and explain the mode of formation and identity of the phosphorus-containing species in the volatiles generated during the Selby-Noack volatility test and to compare these species to those found in both the fresh oil and the residual oil remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The soluble species are reported to be (RO) 2 PSSR, (RO) 2 PSOR, PO(OR) 3 and polyphosphates. Volatile components from ZDDPs also arise from thermal degradation and/or oxidation [8,28]. These studies show that ZDDP is an effective antioxidant, which undergoes degradation and oxidation.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The soluble species are reported to be (RO) 2 PSSR, (RO) 2 PSOR, PO(OR) 3 and polyphosphates. Volatile components from ZDDPs also arise from thermal degradation and/or oxidation [8,28]. These studies show that ZDDP is an effective antioxidant, which undergoes degradation and oxidation.…”
Section: Introductionmentioning
confidence: 86%
“…The thermal degradation products of ZDDP are characterized by 31P NMR [27][28][29][30][31]. It is generally reported that ZDDP thermally degrades very rapidly, generating both soluble and insoluble organo/inorganic phosphorus products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neutral 2-EH ZDDP sample (8.12%P by ICP analysis, 8.04%P theoretical [26] ) was not crystalline and contained several phosphorus-containing impurities (11% of total phosphorus average area by 31 P NMR). These impurities consisted of various sulfides, thiophosphates, and thiophosphoric salts [27] whose appearance did not change as the temperature was varied and thus were not involved in the monomer-dimer equilibrium. The neutral 2-EH ZDDP, 0.040 g, 1.05 mmol total phosphorus, was dissolved in 1 ml CDCl 3 31 P NMR data were obtained using a Gemini 300 NMR spectrometer from Varian operating at 121.477 MHz for phosphorus resonance.…”
Section: Experimental Synthesismentioning
confidence: 99%
“…31P nuclear magnetic resonance (NMR) spectroscopy has been used to analyse the decomposed and soluble phosphorus species generated from the ZDDP oil solution [34][35][36]. The individual phosphorus-containing species are identified by a ''chemical shift'' in the phosphorus-31 peak because of the different chemical environments around the phosphorus atoms in the ZDDP or ZDDP decomposition products compared to the phosphorus atom in phosphoric acid.…”
Section: Introductionmentioning
confidence: 99%